The The Jakarta Scientific Integration Paradigm - Rara Bilqis Salsabila, Iksan (Institut Kariman Wirayudha Sumenep, 2025)
This article examines the paradigm of scientific integration known as the Jakarta School at UIN Syarif Hidayatullah Jakarta, initiated by Azyumardi Azra through the concept of reintegration of sciences. The study focuses on the longstanding dichotomy between religious and secular knowledge in the Islamic world and the need for contemporary Islamic higher education to address modern challenges while maintaining classical traditions. Using a descriptive qualitative literature study, data were collected from books, journal articles, and official documents related to the Jakarta School and Azra’s thought. The findings show that the integration of sciences is realized through ontological, epistemological, and axiological approaches, emphasizing the unity of knowledge sources, interdisciplinary dialogue, and the internalization of Islamic values within academic discourse. Practically, this integration is reflected in curricula that combine classical Islamic traditions with modern sciences in a proportional and dialogical manner. The study concludes that the Jakarta School serves not only as a conceptual discourse but also as a concrete paradigm for Islamic higher education, aiming to produce graduates who are religious, critical, and humanistic, offering an epistemological synthesis that bridges classical Islamic knowledge with contemporary challenges.